Inhibition of Transformation of Bacillus subtilis by Heavy Metals - Groves, David J. (1974)
Mercuric ions, as well as organomercuric ions and cadmium ions, can inhibit deoxyribonucleic acid-mediated transformation in Bacillus subtilis 168 without decreasing the viability of the total population. Differences in the inhibition of transformation by mercuric ions are identifiable on a temporal and concentration dependence basis. Sensitivity to low concentrations (9.2 × 10(−8) M) appears early in the uptake of deoxyribonucleic acid before the transformed markers have become insensitive to deoxyribonuclease. Resistance to “low concentrations” of Hg(2+) is kinetically indistinguishable from the requirement for magnesium in the transformation process. This inactivation is not reversed by the mercury-binding compound glutathione. Sensitivity to mercuric ions at a higher concentration (5.52 × 10(−7) M) occurs after the donor deoxyribonucleic acid has become insensitive to deoxyribonuclease. These complex interactions between mercuric ions and the process of transformation are discussed.